2021
DOI: 10.12932/ap-310119-0485
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of small airways dysfunction in asthma with- and without-fixed airflow obstruction and chronic obstructive pulmonary disease

Abstract: Background: Small airways dysfunction (SAD) is not uncommon in asthma without fixed airflow obstruction (FAO). Objectives:We aimed to determine if SAD in non-FAO asthma is different from FAO-asthma and COPD.Methods: Cases of obstructive airway diseases who underwent spirometry, plethysmography, and impulse oscillometry [resistance at 5 Hz (R 5 ) and at 20 Hz (R 20 ), peripheral resistance (R 5 -R 20 ), and reactance area (AX)] were reviewed, and classified as; 1) COPD, 2) FAO-asthma, and 3) non-FAO asthma. FAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 23 publications
3
12
1
Order By: Relevance
“…At the same time, IPF patients without SAD had no bronchodilator effect. The thresholds for the bronchodilatory test using FOT parameters are a 40% decrease in R and a 50% increase in X [58]. Similarly in COVID survivors, even when spirometry was normal, changes in oscillometric parameters were detected [59].…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, IPF patients without SAD had no bronchodilator effect. The thresholds for the bronchodilatory test using FOT parameters are a 40% decrease in R and a 50% increase in X [58]. Similarly in COVID survivors, even when spirometry was normal, changes in oscillometric parameters were detected [59].…”
Section: Discussionmentioning
confidence: 96%
“…Currently, there is a variety of definitions of FAO used in clinical practice and medical research including use of pre- and/or post-bronchodilator spirometry values, Forced Expiratory Volume in the 1 st second/Forced Vital Capacity ratio (FEV 1 /FVC), absolute or relative cutoffs as well delineation based on the absence of a bronchodilator response alone. Spirometry predominantly assesses the flow of larger more central airways and is not a sensitive measure of the small peripheral airway dysfunction and abnormal mechanical properties of lung tissue that contribute to the pathogenesis of severe asthma [ 8 , 9 ]. In order to assess the small airways and parenchyma in asthma, a number of different techniques have been used [ 8 , 9 , 10 ].…”
Section: Fixed Airflow Obstruction: Is It Due To Asthma Copd or Asthm...mentioning
confidence: 99%
“…Spirometry predominantly assesses the flow of larger more central airways and is not a sensitive measure of the small peripheral airway dysfunction and abnormal mechanical properties of lung tissue that contribute to the pathogenesis of severe asthma [ 8 , 9 ]. In order to assess the small airways and parenchyma in asthma, a number of different techniques have been used [ 8 , 9 , 10 ]. Oscillometry, increasingly utilized both in clinical practice and medical research, does not require effort to force expiration that may affect small airway closure and can differentiate if an increase in the total resistance is located at central or at peripheral airways.…”
Section: Fixed Airflow Obstruction: Is It Due To Asthma Copd or Asthm...mentioning
confidence: 99%
See 1 more Smart Citation
“…In asthma, a systematic review showed that the prevalence of SAD in asthma ranged from 33.0 to 69.9% when using IOS ( 22 ). In one study, the prevalence of SAD by using fixed R5–R20 criteria ≥0.075 kPa/L/s in COPD, asthma with FAO, and asthma without FAO were 68, 95, and 77%, respectively ( 21 ). By using spirometry, Manoharan et al found that 54% of asthma had SAD defined using FEF25–75% of <60% predicted ( 29 ).…”
Section: Introductionmentioning
confidence: 99%